How do intracompetition strategies differ between para powerlifting podium and nonpodium athletes? A retrospective, cross-sectional analysis - Beaumont, P.; Garrett, J.; van den Hoek, D. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to investigate the intracompetition strategies used by para powerlifters and quantify and report them for application by coaches and athletes to improve their odds of competitive success. A cross-sectional retrospective analysis was conducted using a public powerlifting database. Primary analysis categorized athletes as either podium (POD) or nonpodium (NPOD), and a subanalysis classified athletes as either gold medalists (GMs) or silver and bronze medalists (SBMs). Analyses of variance were used to assess the significance of the difference between groups. Pearson's correlations were used to evaluate the magnitude of the relationships and binary logistic regressions were used to quantify the variables. Results are reported as odds ratios, and an alpha level of p < 0.05 was considered statistically significant. There was a significant difference in mean age (POD = 1.6 years younger; p < 0.001), body mass (POD = 2.7 kg heavier; p = 0.006), and best lift (POD = 19.5 kg greater; p < 0.001) for female POD athletes compared with NPOD athletes. For male POD athletes compared with NPOD athletes, there was a difference in mean age (POD = 0.6 years younger; p = 0.035) and best lift (POD = 28.4 kg greater; p < 0.001). Comparing GMs with SBMs showed a significant difference in the mean best lift in both men (GM = 17.4 kg greater; p < 0.001) and women (GM = 11.1 kg greater; p < 0.001). A positive relationship was seen in both the primary and subanalysis between the number of successful lifts (of 3) and an increase in the odds of competitive success (i.e., winning). The findings of this research indicate that high-performing para powerlifters tend to choose attempt weights that prioritize the successful completion of all 3 intracompetition lifts to win a competition.